MEDITASI DAPAT MENURUNKAN TEKANAN DARAH SISTOLIK PADA LANSIA DENGAN HIPERTENSI ESENSIAL - Gunawan, Adi; Subiyanto, Paulus; Erwanto, Fredi (MEDIA ILMU KESEHATAN, 2014)
Background: Hypertension is often called a silent killer. It can cause disorders in the heart, kidney, brain and other vital organs. One of the methods to lower blood pressure is by performing meditation. Catecolamine hormones produced during meditation can make individual feels relaxed. Hence, heart beats slower. Objective: To identify the effect of meditation to the decrease of systolic blood preassure in the middle-aged elderly. Methods:This study was a quasi-experiment with two groups pre- and post-test design. Study was carried out in November 2013 at the village of Sukorejo, Sambirejo, Ngawen, Gunungkidul, Yogyakarta. Respondents of the study consisted of 30 respondents aged 45-59 years old. They were taken through a total sampling technique. Mann-Whitney U Test was employed to analyze the data. Results: The Mann-Whitney U Test showed that the average decrease of systolic blood pressure in the control group was 0,20 and was 14.72 in the intervention group (p<0.05). There was a significant decrease of blood pressure between initial and final assessments in the subject with intervention. Conclusion: There was a significant effect of meditation to the decrease of systolicblood pressure in the middle-aged elderly population. Keywords: Hypertension, Meditation, Middle-Aged Elderly